Eksistensi Asosiasi Fintech Dalam Pengawasan Peer To Peer (P2P) Lending - Almaududi Almaududi; Ihsani Mazelfi (Faculty of Law, Andalas University, 2021)
Financial Services Authority Regulation Number 77 / POJK.01 / 2016 and Number 13 / POJK.02 / 2018 not only regulated the Fintech P2P Lending's operational activities but also became the basis for the creation of the Fintech Association. Based on Article 48 POJK 77/2016 jo. Article 21 POJK 13/2018, OJK appoints a Fintech Association (AFPI) which functions to establish a Code of Ethics and provides several regulations that have not been regulated by OJK. In this connection, problems arise related to order, the role and function of the Fintech Association in monitoring Fintech P2P Lending. It is worth questioning the basis and consideration of the OJK in establishing and making the Fintech Association an institution that joins Fintech P2P Lending. It is also necessary to analyze the extent to which the role or existence of the Fintech Association in realizing a balance between the principles of consumer protection and prudence with innovation and competition.